Comparison of four meta-heuristic algorithms for optimal design of double-layer barrel vaults. Issue 3 (September 2018) - Kaveh, Ali; Ilchi Ghazaan, Majid; Mahjoubi, Soroush
Barrel vaults are effective semi-cylindrical forms of roof systems that are widespread for multipurpose facilities including warehouse, rail station, pools, sports center, airplane hungers, and community centers because of providing long-span and economical roof with significant amount of space underneath. In the present study, size optimization of double-layer barrel vaults with different configurations is studied. Four recently developed algorithms consisting of the CBO, ECBO, VPS, and MDVC-UVPS are employed and their performances are compared. The structures are subjected to stress, stability, and displacement limitations according to the provisions of AISC-ASD. The design variables are the cross-sectional areas of the bar elements which are selected from steel pipe sections. The numerical results indicate that the MDVC-UVPS outperforms the other algorithms in finding optimal design in all examples.